2017
DOI: 10.3389/fnmol.2017.00219
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of miR-21 on Pain and Associated Affective and Cognitive Behavior after Spared Nerve Injury in B7-H1 ko Mouse

Abstract: MicroRNAs (miRNAs) are increasingly recognized as regulators of immune and neuronal gene expression and are potential master switches in neuropathic pain pathophysiology. miR-21 is a promising candidate that may link the immune and the pain system. To investigate the pathophysiological role of miR-21 in neuropathic pain, we assessed mice deficient of B7 homolog 1 (B7-H1), a major inhibitor of inflammatory responses. In previous studies, an upregulation of miR-21 had been shown in mouse lymphocytes. Young (8 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 68 publications
3
21
0
2
Order By: Relevance
“…Their observations showed high levels of transcriptional activity in dorsal root ganglia (DRG) following nerve injury in adulthood compared to nerve injury in early life, sustained the reduced incidence of neuropathic pain in infants. Macrophages and lymphocytes invasion into the peripheral nerve has been observed 1 week after SNI [77]. The contribution of T cells in SNI-induced pain has been reported by Costigan and coll.…”
Section: Role Of Glia and Immune Cells In The Sni Modelsupporting
confidence: 52%
See 1 more Smart Citation
“…Their observations showed high levels of transcriptional activity in dorsal root ganglia (DRG) following nerve injury in adulthood compared to nerve injury in early life, sustained the reduced incidence of neuropathic pain in infants. Macrophages and lymphocytes invasion into the peripheral nerve has been observed 1 week after SNI [77]. The contribution of T cells in SNI-induced pain has been reported by Costigan and coll.…”
Section: Role Of Glia and Immune Cells In The Sni Modelsupporting
confidence: 52%
“…Impairment in cognitive flexibility was also detected in mice in the attentional rule-shifting task 21 days after SNI surgery [76]. Curiously, no impairment in spatial working memory was found in the Morris water maze 3 to 21 days after SNI in mice by Karl et al [77]. All the evidence described so far highlights close comorbidity existing between neuropathic pain in general and the SNI model in particular and disturbances of affectivity and cognition.…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 93%
“…In the case of examining chronic pain with the effects of age in mind, if the specific emotional pain pathway (superficial dorsal horn‐thalamus and surrounding cortices) is strengthened neuronally from a young age, then a child's brain may be “wired” to respond to pain at lower levels of stimulation as discussed above (Karl et al, ). This same phenomenon, may also explain why men and women respond to pain differently, such that women from a young age are conditioned socially to react emotionally to pain (they may cry in their parents arms and be comforted) versus boys who are taught to “be tough” ( they may not be emotionally comforted by a parent).…”
Section: Contributing Social Factorsmentioning
confidence: 99%
“…While a great deal still remains in fully understanding the modification of miRNA, Sakai and Suzuki (2013) found that an increase in miR-21 was correlated with an upsurge in neuropathic pain behaviors in mice. Other researchers (e.g., Karl, Grießhammer, Üçeyler, & Sommer, 2017) have also highlighted the specific role that increased miR-21 regulation plays with regard to chronic pain.…”
Section: B I Olog I C Al Fac Tor Smentioning
confidence: 99%
See 1 more Smart Citation